Association of COVID-19 stimulus receipt and spending with family health - Emma M. Reese; Noah Lines; Evan L. Thacker; Michael D. Barnes (PLoS ONE, 2025)
In this study, we aimed to determine the impact of U.S. government stimulus payments on family health during the COVID-19 pandemic. We hypothesized that receiving stimulus checks is associated with better family health and the effect of stimulus check receipt differs by income level. Additionally, we hypothesized that spending on immediate needs and paying off loans is associated with worse family health, and the effects of this spending differ by income level. Participants included 456 registered Amazon Mechanical Turk (mTurk) users, stratified by income, marital status, and parental status. We used the Family Health Scale – Long Form to measure family health constructs: social-emotional health, healthy lifestyle, health resources, and social support. For all statistical analyses, we used SAS Studio 3.8. We performed an exploratory factor analysis to determine six spending profiles: loans, savings, housing, household supplies, durable goods, and medical costs. After adjustment, our multiple linear regression model found that mean family health and social-emotional health scores were higher among individuals who received all three checks, but this did not differ by income category. Mean family health and social-emotional health were lower among individuals who spent more significant portions of their stimulus checks on housing, household supplies, and medical costs. Spending greater portions of checks on medical costs was associated with lower scores among every family health construct except family healthy lifestyle. Among mid-to-high-income participants, family health scores were significantly lower, with more spending on housing, household supplies, durable goods, and medical costs, with similar results in the subscale scores. The reduction of family health scores with spending on medical costs and durable goods were more pronounced among the mid-to-high-income group than the low-income group. Stimulus payments may be a promising family policy method for improving overall family health; however, more research should address the differences between income groups and government assistance.